Application of Physics E-Learning Material Integrated Social-Scientific Issue Context to Improve Students’ Scientific Literacy Skills - Rhoudatul Annisa; Asrizal Asrizal; Werina Werina (Universitas Negeri Padang, 2023)
Conceptual understanding and scientific literacy of science are important part for students. Through a good understanding of scientific concepts and literacy, it is easier for students to learn new material and solve the problems they face. The purpose of this research is to improve students' learning Literacy through E-teaching materials with the context of Social-Scientific Issue (SSI). The research method used is Classroom Action Research with the Kemmis and Mc Taggart action research model. The research was conducted at SMA N 3 Padang in March 2023. The research subjects were students of class X E 3 in the 2022/2023 academic year with a total of 35 students. Data collection techniques in this study were observation and tests. Data analysis techniques in quantitative and qualitative descriptive research. The results of classroom action research were carried out in 2 cycles with the stages of planning, implementing, observing and reflecting. The use of the e-learning material in the context of Social-Scientific Issue (SSI) can improve students' ability to understand concepts and scientific literacy skills on Renewable Energy material. Therefore, e-teaching material can be used by physics teachers to improve the students’ conceptual understanding and scientific literacy.